A critical evaluation of oil extraction and fatty acid composition of Prosopis Julifera. (2020) - Rajeshwaran, M.; Ramasamy, S.; Parthasarathi, R.; Ponshanmugakumar, A.
Abstract: The aim of the present investigation is to find a better replacement to edible oils. Prosopis Julifera (non-edible feedstock) is one of the important tree species in the arid and semi arid zones of the world. The fruits (Pods) of Prosopis Julifera were cleaned, cracked and powdered before oil extraction. Extraction of oil from Prosopis Julifera was carried out by soxhlet apparatus using different solvents at 3:1 to 9:1 (w/v) solid to solvent ratios and the extraction time periods were 3–10 (hrs). Polar and non-polar solvents such as Petroleum Ether, n-Pentane, Ethyl acetate, Iso-propanol, Hexane, Methanol, and Ethanol were used. Using gas chromatography (GC), Fatty acid methyl esters were separated, identified and quantified. In order to analyse the qualitative nature of the oil extracted, performance of different solvents in terms of Saponification value, Acid value, Iodine value, refractive index and free fatty acids were determined by suitable tests. The test results indicate that irrespective of the solvent used, the oil yield was found be increasing when there is the increase in the solid to solvent ratio, reaction time period and reaction temperature. However the maximum amount of oil yield 36.9% was obtained using methanol at the solid to solvent ratio of 1: 9 (w/v), the reaction temperature of 60 °C for a time period of 9 (hrs). Hence it can be concluded that the oil produced from the non edible Prosopis Julifera could be a best alternate in the future days to come.